Restoring of Vertical Dimension in a Patient with Retrodiscal Pressure - Artigas Sandoval TD, EPB, MCNM, Beatriz Elena (2018)
When oral rehabilitation is performed, an important consideration is to reach an orthopedic stabilization, at the end of the treatment. This condition depends on the Temporomandibular Joint and all neuroclusomuscular components. To achieve this, it is necessary to take into account different parameters such as centric occlusion and vertical dimension. In doing so, we decrease the likelihood of different neuroclusomuscular problems, such as Temporomandibular Joint Disorders, Bruxism, periodontal problems, abfractions, fracture of restorations, among others.